Dynamical Theory of Triple-Crystal X-ray Diffractometry and Characterization of Microdefects and Strains in Imperfect Single Crystals - Molodkin, V.B.; Olikhovskii, S.I.; Len, E.G.; Kyslovskyy, Ye.M.; Reshetnyk, O.V.; Vladimirova, T.P.; Sheludchenko, B.V.; Skakunova, E.S.; Lizunov, V.V.; Kochelab, E.V.; Fodchuk, I.M.; Klad’ko, V.P. (Металлофизика и новейшие технологии, 2016)
A short review of basic principles and limitations in obtaining the analytical expressions for the coherent and diffuse scattering intensities measured by the triple-crystal diffractometer (TCD) are presented. Explicit analytical expressions are given for both the diffuse components of TCD profiles and the reciprocal-lattice maps measured within the Bragg diffraction geometry from crystals containing microdefects of several types. These formulas are derived by using the generalized dynamical theory of X-ray scattering by imperfect crystals with randomly distributed microdefects. Some examples demonstrating possibilities of the developed theory for quantitative characterization of structural imperfections in real single crystals are represented. In particular, characteristics of the complicated microdefect structures fabricated in various silicon crystals grown by Czochralski technique and floating-zone melting method are determined by analytical treatment of the measured TCD profiles, rocking curves, and reciprocal space maps.